Cine y realidad en Gaspar Noé - Gamarra Reyes, Kiandra (2021)
Gaspar Noé, a French-Argentine director, is known for the controversial themes and scenes in his filmography, where violence is the first thing that stands out. However, other elements can be identified that have equal relevance in the structure of his films. The human body is one of them. Noé presents the pleasure and suffering of his characters closely so that the viewer perceives them first-hand. He seeks to shock the viewer with scenes that are difficult to see and hear. The director exhibits things in a transgressive way to show the malaise that exists within France. This thesis offers a study on the construction of reality in cinema, the representation of French society, the New French Extremism and the social, political and economic context of France, which will allow a better understanding of its environment, the audiovisual language that uses and the references that have influenced his style. Likewise, these points will serve as the basis for analyzing the director's filmography. The analysis carried out shows that Gaspar Noé, from the beginning, exhibits a pessimistic reality that is reinforcing it over the years by showing a society that is crumbling, unhappy people whose actions are irreversible and the inevitability of destiny. This study enriches realism in film, incorporating the unconventional reality of Gaspar Noé.